III: Three years into the pandemic: What changed in Delhi's electronic bazaars. (February 2022) - Deka, Maitrayee
The initial impressions from Delhi's Lajpat Rai Market, Palika Bazaar and Nehru Place have been that they integrated into the digital economy as suppliers and service providers to e-commerce platforms during COVID times. The increasing use of digital payments to boost online sales, including social media marketing on Facebook and YouTube, has also brought many of them inside a banking system. As a result, physical bazaars are now less about informal face-to-face commerce and operate more as repair hubs and ancillaries to a platform economy.